Text messages for influenza vaccination among pregnant women: A randomized controlled trial. Issue 5 (1st February 2017) - Yudin, Mark H.; Mistry, Niraj; De Souza, Leanne R.; Besel, Kate; Patel, Vishal; Blanco Mejia, Sonia; Bernick, Robyn; Ryan, Victoria; Urquia, Marcelo; Beigi, Richard H.; Moniz, Michelle H.; Sgro, Michael
Abstract: Objective: To evaluate if text message reminders increase the likelihood of receiving the influenza vaccine among pregnant women. Methods: Pregnant women were randomized to either receive or not receive weekly text messages. Women were told the messages would be about health-related behavior in pregnancy. Those randomized to the intervention group received two messages weekly for four consecutive weeks reinforcing that the influenza vaccine is recommended for all pregnant women and safe during pregnancy and breastfeeding. Women were contacted six weeks postpartum to determine if they had received the vaccine. Sample size calculation determined that 108 women were required in both groups to see a 75% increase in vaccination rates over baseline in the text message group compared to the control group. Results: Recruitment began November 4, 2013, and 317 women were randomized. The mean gestational age at recruitment was 22 weeks. There were 40/129 (31%) women in the text message group and 41/152 (27%) women in the control group who received the vaccine (p = 0.51). Significant predictors of vaccine acceptance were being married compared to single (95% vs. 67%, p < 0.001), having higher household income (55% vs. 39%, p = 0.03) and having received the vaccine before (77% vs. 36%, p < 0.001). Among women receiving text messages, the majority were satisfied, with only 15/129 (12%) reporting that they did not like receiving the messages, and 24/129 (19%) stating that the information in the messages was not helpful. Conclusion: Weekly text messages reinforcing the recommendation for and safety of the influenza vaccine in pregnancy did not increase the likelihood of actually receiving the vaccine among pregnant women. Overall vaccination rates were low, highlighting the need for patient education and innovative techniques to improve vaccine acceptance. Registered with ClinicalTrials.gov athttp://www.clinicaltrials.gov, registration numberNCT 02428738 .